Numerical Simulation of the Dynamic Responses of Electric Power Fitting of Transmission Lines after Ice Shedding - Zhongfei Ye; Chuan Wu; Xiaohui Liu; Fei Huang (Shock and Vibration)
As the key connecting components between tower and conductors, electric power fittings play an important role in the provision of the safe operation of transmission lines. Taking 500 kV transmission lines as the research object, electric power fittings failure in heavy icing areas is studied. The following three questions are considered: first, the influence of different ice-shedding methods on the tension of quad bundle conductors; second, the influence of the spans number, span length, height difference, and ice thickness on the conductor tension under the most dangerous ice-shedding mode; lastly, the mechanical characteristics of tension string and suspension string under ice-shedding condition in the stable wind. The results show that the von Mises stress of the parts that connect with the iced conductor in the tension string model is greater than those of the parts connected with the ice-shedding conductor. What is more, the shackle is the most vulnerable part of the whole model, which is prone to wear and damage, and the failure is most likely to occur at the upper shackle. The middle part in the rectangular hanging plate which is connected with the iced conductor is prone to damage, for its maximum stress has already exceeded the yield stress, with a danger degree inferior only to the shackle. In the suspension string model, the von Mises stress of each part is relatively small and does not reach the yield stress. Similarly, the shackle is most likely to be damaged in the overall model, while other parts maintain larger safety margins. The structure of the parts with smaller stress can be optimized according to the simulation results where design margins may be reduced and additional cost benefits realized.